A methodology to address social concerns on electricity planning - Ribeiro, Fernando (2011)
The topic Sustainable Development has brought a wide discussion across a number of sectors in our society, namely in Power Systems. Given the need to address other concerns than the economic ones, decision makers must take into account the rationale that lies beneath strategic choices, such as investing in generation technologies using renewable energy or rather doing business as usual and installing fossil fuel power plants. In this paper logic models were used as a decision-aid supporting tool, with the aim of contributing to explain the connection between building a given power plant and assessing its possible impacts in terms of sustainable development. All the electricity generation technologies were grouped in thermal, renewable energy sources (RES) and nuclear. The literature review fed the construction of three technology generation groups inference and relational diagrams to allow the visualization of environmental, social and economic causes and effects. The results of the literature review and of a set of interviews with experts, based on the diagrams, allowed to conclude that the use of RES have wider positive social impacts on the long run, despite their short-term higher costs compared to the traditional groups (nuclear and thermal).